2(x-3)=7x+14

Simple and best practice solution for 2(x-3)=7x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)=7x+14 equation:



2(x-3)=7x+14
We move all terms to the left:
2(x-3)-(7x+14)=0
We multiply parentheses
2x-(7x+14)-6=0
We get rid of parentheses
2x-7x-14-6=0
We add all the numbers together, and all the variables
-5x-20=0
We move all terms containing x to the left, all other terms to the right
-5x=20
x=20/-5
x=-4

See similar equations:

| 63=−7d+7 | | 7b-18=12+5b | | P(x)=48 | | 2x+5+x=5x+2 | | 6x=78+24 | | 3y=45-5y | | b/10=-15 | | 4/5=-4/7•m | | -0.8x=10.4 | | 3^x-5=76 | | -4(5x+7)-2=-94 | | -x+10x3=7 | | -2(x-10)=36 | | 3x-2=3 | | 6=3(x-3)-6x | | -1.2(3x-3)=4(3x+0.9)= | | 5x=-84 | | -30=4u-2 | | -11p-18=-10p | | 10x-{4x-(5-x)}+3=x-16 | | 79=-5d+9 | | 0=-3/2n+23/6n | | b/16=17 | | 16=25/6x-24 | | 9+9n=9 | | 14-n-7=5n=1 | | 15-8n=3(n-6) | | -4(5x+3)-2=-94 | | 2.4+0.44x=19+1.69x | | 6(x+13)=-2(x+31) | | 3m-4=6-m | | 7|x+5|=-3 |

Equations solver categories